A Case Study on Fiber Bragg Gratings for Biomedical Applications - Bhat, Bindu P.; K.V., Dr.Padmaja (International Journal of Emerging Trends in Science and Technology, 2014)
This paper discusses the various techniques available for the fabrication of fiber Bragg gratings (FBG) and the most efficient method to fabricate FBGs for biomedical applications. The sensors were fabricated using the phase mask technique and the response was tested. The fabricated bare FBG sensors showed a Bragg wavelength reflectivity around 1547.8nm and the etched FBG sensors showed a Bragg wavelength reflectivity around 1546.5nm when connected to Micron Optics Interrogator. The paper also discusses the further scope of the FBG applications in biomedical and biosensing fields. Keywords: Fiber Bragg gratings, fabrication, Phase mask technique, Bragg wavelength, biosensing